Advancing human rights in legally plural Africa: the role of development actors in the justice sector - Corradi, Giselle (Afrika Focus, 2013)
This dissertation examines the role of justice sector aid in sub-Saharan Africa regarding the relationship between human rights and local legal orders from a normative and empirical point of view. At the normative level, it explores how socio-legal theory on legal pluralism and human rights’ cross-contextual implementation may inform the practice of development actors in the justice sector. Based on case studies in Sierra Leone and Mozambique, the research applies this body of knowledge to the analysis of empirical data on development actors’ policies and interventions. The conclusion argues that the following issues deserve particular attention: the adoption of a users’ perspective regarding which local justice providers are targeted by policies and interventions, consideration of how different modes of dispute processing relate to the implementation of human rights, engagement with local knowledge and a critical approach to human rights cross- contextual application. Key words: Justice sector aid, human rights, access to justice, legal pluralism, customary legal orders, Sierra Leone, Mozambique